A The success of a company to be able to achieve a good level of performance is certainly influenced by internal and external factors of human resources with different levels. Every company has the hope to achieve the optimization of the work of employees - Didit Darmawan (Jurnal Ilmiah Satyagraha, 2022)
A The success of a company to be able to achieve a good level ofperformance is certainly influenced by internal and external factors of humanresources with different levels. Every company has the hope to achieve theoptimization of the work of employees and to achieve effectiveness and efficiencyin accordance with organizational goals. This study will observe motivation,ability, experience, involvement, discipline as internal factors of employees.Furthermore, it is analyzed and determined the role of each of these internalfactors on employee performance. The sample is set as many as 100 respondentstaken from employees in the production department as operators. The analysistool is multiple linear regression analysis. From the results of the study, it isevident that the variables of motivation, ability, experience, involvement anddiscipline have a significant influence partially or simultaneously on employeeperformance.